Forming an Affiliation Between Two Culturally Different Academic Institutions of Nursing Studies - Ronen Segev RN, PhD; Ester Strauss RN, PhD (SAGE Publishing, 2020)
Introduction This article describes the association of two culturally different institutions opening a joint Bachelor of Science in Nursing (BSN) program for ultra-Orthodox Jewish (Haredi) women in order to enable them to find jobs due to changes in their society and increasing global demand for nurses in the labor market. The objective of this description is to illustrate the efforts and changes needed to facilitate the affiliation of two culturally and ideologically different organizations and the implications and conclusions of such a program. Methods The study is based on interviews with past administrators, a review of the literature, and supporting institution documents. Conclusions A joint nursing academic program was founded by two culturally different educational institutions for the ultra-Orthodox Jewish women population. Creating a culturally sensitive nursing academic program helped ultra-Orthodox women acquire an academic profession which enabled their integration into the academic professional's work world and add more nurses to the labor market. The authors reviewed the efforts and changes needed to facilitate the affiliation of two culturally and ideologically different organizations based on the Bolman and Deal four frames model.